Diversity‐Oriented Synthesis of Diol‐Based Peptidomimetics as Potential HIV Protease Inhibitors and Antitumor Agents. (6th July 2018) - Vadhadiya, Paresh M.; Jean, Marc‐Alexandre; Bouzriba, Chahrazed; Tremblay, Thomas; Lagüe, Patrick; Fortin, Sébastien; Boukouvalas, John; Giguère, Denis
Abstract: Peptidomimetic HIV protease inhibitors are an important class of drugs used in the treatment of AIDS. The synthesis of a new type of diol‐based peptidomimetics is described. Our route is flexible, usesd ‐glucal as an inexpensive starting material, and makes minimal use of protection/deprotection cycles. Binding affinities from molecular docking simulations suggest that these compounds are potential inhibitors of HIV protease. Moreover, the antiproliferative activities of compounds33 a, 35 a, and35 b on HT‐29, M21, and MCF7 cancer cell lines are in the low micromolar range. The results provide a platform that could facilitate the development of medically relevant asymmetrical diol‐based peptidomimetics. Abstract : Sweet peptidomimetics : We have prepared a new type of diol‐based peptidomimetics by starting fromd ‐glucal. Molecular docking simulations suggest that these compounds are potential inhibitors of HIV protease. Antiproliferative activities exhibited significant total growth inhibition and LC50 values, showing potent antitumor potencies.